Modeling and Optimization of Teachers' Organizational Commitment Strengthening - Anisa Andiana; Soewarto Hardhienata; Rais Hidayat (Green Publisher Indonesia, 2024)
This study aims to find strategies to strengthen the Organizational Commitment of Teachers by analyzing the influence of variables that have a positive and dominant effect on Teacher Organizational Commitment. The research was conducted in 7 State MTs (Islamic Junior High Schools) in Cianjur Regency with a sample of 138 civil servant teachers. This research uses the POP-SDM approach (Modeling and Optimization of Management Resources) with SITOREM analysis to generate optimal solutions from the existing solutions. From this research, it was found that there is a positive and significant influence of transformational leadership on teacher organizational commitment with a standard factor loading value of 0.16, work climate on teacher organizational commitment with a standard factor loading value of 0.27, professional attitude towards teacher organizational commitment with a standard factor loading value of 0.50, transformational leadership on professional attitude with a standard factor loading value of 0.33, work climate on professional attitude with a standard factor loading value of 0.52. Meanwhile, the optimal solution obtained is that all indicators need to be improved with the priority order of improvements as follows: having a sense of responsibility, being enthusiastic about learning, pride in the profession, support from superiors, openness among teachers, high tolerance, freedom of expression, exemplary behavior, raising awareness of vision and mission, inspiration, charisma, responsibility, loyalty, seriousness, and the desire to stay in the organization. The implication of the research is that if organizational commitment is to be strengthened, development is needed in transformational leadership, work climate, and professional attitude.